A teaching look at the evaluation processes in the school context (Research, Society and Development, 2019)
This article aims to investigate and discuss the evaluation processes in teaching, how the evaluations are being understood, and what is the role of the school in the vision of two teachers of a State Institute of Education in the modality of Normal Course . The methodological delineation of this research follows a qualitative approach and for the data collection a questionnaire was composed, consisting of five open questions. As a result, it was evidenced that the participants / teachers are concerned with the methodologies currently still present in the classroom, which indicates that they are willing and flexible in the face of this constant challenge of changing design and practices. As well, it is necessary that the evaluation processes for the learning need to be rethought in the school contexts, because the practices used still do not present if the student has been learning.